PREFERENCE OF DAIRYWOMEN OF HIMACHAL PRADESH FOR TRAINING PROGRAMME - Gupta, Manoj; Verma , H K; Kansal , S K; Kasrija, Rajesh (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
The present study was conducted with the objectives to know the duration, place and season needed for training programmes as expressed by the dairywomen in Solan district of Himachal Pradesh. A total of 1000 respondents of Self Help Groups (SHGs) were selected from 50 villages, 20 each from 10 selected villages of five blocks of Solan district. It was observed that more than 60% of the trainees preferred two-week duration of training at the training centre at Solan. More than 90% preferred summer season for training programme.